Redescription of Anastatus mantoidae Motschulsky, the type species of Anastatus Motschulsky 1859, and Anastatus echidna (Motschulsky), the type species of Cacotropia Motschulsky 1863, with respect to taxonomy of Anastatus (Hymenoptera: Eupelmidae: Eupelminae) - Gibson, Gary A. P. (Zootaxa, 2020)
Both sexes of Anastatus mantoidae Motschulsky, the type species of Anastatus Motschulsky, 1859, and females of Anastatus echidna (Motschulsky), the type species of Cacotropia Motschulsky, 1863, the oldest junior synonym of Anastatus (Hymenoptera: Eupelmidae: Eupelminae), are redescribed and illustrated based on original type material and compared to more recently collected material. Anastatus mantoidae, previously known only from Sri Lanka, is newly reported from Indonesia (Java and Sumatra) and Thailand, and a very similar species, A. motschulskyi n. sp., is newly described based on both sexes from Malaysia (Sabah) and Thailand and compared to A. mantoidae. Anastatus echidna, also originally known only from Sri Lanka, is newly reported from India, Pakistan and Thailand, and potential synonymy of one or both of Anastatus amarus (Subba Rao, 1957) and Anastatus acherontiae Narayanan, Subba Rao & Ramachandra Rao, 1960, under A. echidna is discussed.